Feto-Maternal Outcome in Patients with Placenta Previa at Aljala Maternity Hospital, Tripoli, Libya - Laylay Ammar; Nasreen Osman; Amel Morgham; Noha Alshawish (AlQalam Journal of Medical and Applied Sciences, 2024)
To assess maternal and fetal morbidity associated with placenta previa. All patients with placenta previa who delivered in services hospital, Aljala Maternity hospital during the years 2020 to 2022 were involved. This study designed as descriptive retrospective cross-sectional study. Total number of 55 patients having placenta previa during the study period, 52.07% of patients were in age group 31-40 years while 15.5% of patients with placenta previa were less than 30 years (p<0.05). Regarding the gestational age, the current study showed that the mean gestational age for the patients who had PP was 37.19 weeks. The result was statistically insignificant with p value of 0.618. Most of the patients had H/O previous cesarean section (15 previous I C/S, 26 previous II C/S, 3 previous III C/S, 2 previous IV C/S, and 1 previous V C/S) which accounts 86.1% of the participated patients. Increased number of caesarean sections significantly associated with PP (p=0.0001). Around two third of women underwent urgent C/S (66%), and the rest of them (34%) had elective type. One third of the patients came with H/O vaginal bleeding. 21% of the patients had a complain of pain (most of them lower abdominal pain). 12.7% of the patients came shocked. Four percent of the participated women underwent hysterectomy, one of them had elective cesarean section. 15% of the patients had intrapartum bleeding, and 24% of the participated women had blood transfusion which reach 6 units in one case. With regard the birth weight, most of the neonates had average birth weight (80.4%). The percentage of low birth weight (LBW) was 9.4%. On the other hand, the percentage of macrosomia (birth weight is above 4.5kg) was 10.2% for the P value 0.737. 41.5% of the neonates had H/O admission to the neonatal intensive care unit. The most of the neonates were with mother (58.5%). There was one neonatal death during the admission in NICU. Placenta previa is danger to both the mother and the baby with high maternal morbidity and adverse perinatal outcome. Regular antenatal care with adequate arrangement of blood transfusion and multidisciplinary approach can reduce maternal morbidity and mortality. لتقييم مراضة الأم والجنين المرتبطة بالمشيمة المنزاحة. تمت مشاركة جميع مريضات المشيمة المنزاحة اللاتي ولدن في مستشفى الخدمات، مستشفى الجلاء للولادة خلال الأعوام من 2020 إلى 2022. صممت هذه الدراسة كدراسة وصفية استرجاعية مقطعية. إجمالي عدد 55 مريضة مصابة بالمشيمة المنزاحة خلال فترة الدراسة، 52.07% من المرضى كانوا في الفئة العمرية 31-40 سنة بينما 15.5% من المرضى الذين يعانون من المشيمة المنزاحة كانوا أقل من 30 سنة (P <0.05). وفيما يتعلق بعمر الحمل، أظهرت الدراسة الحالية أن متوسط عمر الحمل للمرضى الذين لديهم PP كان 37.19 أسبوعا. وكانت النتيجة ذات دلالة إحصائية بقيمة p 0.618. معظم المرضى خضعوا لعملية قيصرية سابقة (15 I C/S سابقة، 26 II C/S سابقة، 3 III C/S سابقة، 2 IV C/S سابقة، و1 V C/S سابقة) وهو ما يمثل 86.1٪ من المرضى المشاركين. زيادة عدد العمليات القيصرية المرتبطة بشكل كبير بـ PP (ع = 0.0001). حوالي ثلثي النساء خضعن لعملية C/S عاجلة (66%)، والباقي منهن (34%) من النوع الاختياري. ثلث المرضى جاءوا مع نزيف مهبلي H/O. 21% من المرضى اشتكوا من الألم (معظمهم آلام في أسفل البطن). 12.7% من المرضى أصيبوا بالصدمة. خضعت أربعة بالمائة من النساء المشاركات لعملية استئصال الرحم، وخضعت إحداهن لعملية قيصرية اختيارية. 15% من المرضى أصيبوا بنزيف أثناء الولادة، و24% من النساء المشاركات خضعن لعمليات نقل دم تصل إلى 6 وحدات في الحالة الواحدة. وفيما يتعلق بالوزن عند الولادة، فإن معظم الولدان كان متوسط وزنهم عند الولادة (80.4%). وبلغت نسبة انخفاض الوزن عند الولادة 9.4%. في المقابل بلغت نسبة العملقة (الوزن عند الولادة أكثر من 4.5 كجم) 10.2% للقيمة P 0.737. تم إدخال 41.5% من الأطفال حديثي الولادة إلى وحدة العناية المركزة لحديثي الولادة. معظم المواليد كانوا مع أمهاتهم (58.5%). كانت هناك حالة وفاة واحدة لحديثي الولادة أثناء القبول في وحدة العناية المركزة لحديثي الولادة. تشكل المشيمة المنزاحة خطراً على كل من الأم والطفل مع ارتفاع معدلات الإصابة بالأمراض لدى الأمهات ونتائج سلبية في الفترة المحيطة بالولادة. الرعاية السابقة للولادة المنتظمة مع الترتيب المناسب لنقل الدم واتباع نهج متعدد التخصصات يمكن أن تقلل من معدلات المراضة والوفيات النفاسية.